2013
DOI: 10.1128/jb.00853-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a DNA-Damage-Inducible Regulon in Acinetobacter baumannii

Abstract: dThe transcriptional response of Acinetobacter baumannii, a major cause of nosocomial infections, to the DNA-damaging agent mitomycin C (MMC) was studied using DNA microarray technology. Most of the 39 genes induced by MMC were related to either prophages or encoded proteins involved in DNA repair. Electrophoretic mobility shift assays demonstrated that the product of the A. baumannii MMC-inducible umuD gene (umuDAb) specifically binds to the palindromic sequence TTGAAAATGTAAC TTTTTCAA present in its promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
74
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 20 publications
6
74
1
Order By: Relevance
“…baumannii contains multiple umuDC operons and unlinked umuC and umuD genes, all of which encode components of errorprone DNA polymerase V (6). In A. baumannii strain ATCC 17978, the induction of these components after DNA damage leads to the introduction of point mutations in the bacterial genome, including those able to generate antibiotic resistance (7,8). Previous studies showed that the umuD and umuC genes of A. baumannii are induced by ciprofloxacin, which is also a strong inducer of the SOS response (6).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…baumannii contains multiple umuDC operons and unlinked umuC and umuD genes, all of which encode components of errorprone DNA polymerase V (6). In A. baumannii strain ATCC 17978, the induction of these components after DNA damage leads to the introduction of point mutations in the bacterial genome, including those able to generate antibiotic resistance (7,8). Previous studies showed that the umuD and umuC genes of A. baumannii are induced by ciprofloxacin, which is also a strong inducer of the SOS response (6).…”
mentioning
confidence: 99%
“…Previous studies showed that the UmuDAb regulon, encoding several error-prone DNA polymerase V subunits, is an important component of the SOS response and mutagenesis in A. baumannii (6)(7)(8). Point mutations in the bacterial genome caused by these error-prone DNA polymerases can result in the acquisition of drug resistance.…”
mentioning
confidence: 99%
See 3 more Smart Citations